Imagining numbers : (particularly the square root of minus fifteen) - Mazur, Barry (New York : Farrar Straus Giroux, 2003)
A tour of the creative side of mathematics describes the first use of imaginary numbers in sixteenth-century Italy and the subsequent two-hundred-year effort to perfect the process, citing the words of key Renaissance thinkers.
Includes bibliographical references (p. [257]-258) and index.
Keywords: Numbers, Complex